Quality of life, perceived stress and nutrition of patients with irritable bowel syndrome: A descriptive study - Çelik, Zehra Margot; Aktaç, Şule; Sabuncular, Güleren; Dirican, Tuğçe; Demir, Aleyna Habibe (The North African Journal of Food and Nutrition Research, 2022)
Background: Irritable Bowel Syndrome (IBS) is a chronic and common functional bowel disorder that currently has no definite treatment. Depending on the type and severity of the individual’s symptoms, medication, diet, and/or lifestyle changes are recommended. Aims: This study aimed to determine the relationship between the quality of life, perceived stress levels, and nutrition of individuals diagnosed with IBS. Subjects and Methods: Between March 2020 and March 2021, 340 patients with IBS volunteered for this study. The demographic information questionnaire, Irritable Bowel Syndrome Quality of Life (IBS-QOL) scale, Perceived Stress Scale-14 (PSS-14), and Food Frequency Questionnaire were applied via an online form. Results: From the 340 patients, 230 were eligible. Out of them, 27% followed a special diet for IBS. When the IBS-QOL scores of men were compared according to their educational status, the scores of those with a high school or higher education level (109.7±32.8) were found to be higher than those with a lower education level than high school (95.4±17.5) (p=0.008), while the educational status of women did not affect the IBS-QOL scores (p>0.05). The mean IBS-QOL score of men was 44.8 ± 20.1 and lower than women (50.9±21.7) (p=0.030). The mean IBS-QOL score of women following an IBS-specific diet was 57.6 ± 22.6 and higher than women who did not follow an IBS-specific diet (48.2±20.9) (p=0.023). The IBS-QOL scores of women with gluten or lactose intolerance were lower than women without any intolerances (p=0.004). The mean IBS-QOL score for women with lactose intolerance was higher than those with gluten intolerance (p=0.004). When the IBS-QOL scores were evaluated according to the frequency of food consumption, no significant differences were found in the food groups (p>0.05). In this study, no significant correlation was found between IBS-QOL scores and PSS-14 scores (p>0.05). Conclusions: The prediction equations developed for healthy populations are not accurate enough to determine the energy requirements in SCD.